Divination and Human Nature : A Cognitive History of Intuition in Classical Antiquity - Struck, Peter T. (Book collections on Project MUSE., 2018)
This volume casts a new perspective on the rich tradition of ancient divination - the reading of divine signs in oracles, omens and dreams. It shows how philosophers of the classical era interpreted the phenomena of divination as a practice closer to intuition and instinct than magic.